Penerapan Model Student Facilitator And Explaining Terhadap Peningkatan Kemampuan Berbicara Siswa Kelas X.1 MA Muhammadiyah Sombala Bella Kab.Takalar - Indramini Indramini (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
This research aims to improve the speaking skills of class X.1 students at MA Muhammadiyah Sombala Bella, Takalar Regency through the Student Facilitator and Explaining model. The subjects of this research were 30 students in class The results of the research showed that there was an increase in students' speaking skills from cycle I to cycle II, namely an increase in the number of students listening to the teacher's explanation, collaborating in groups, asking questions and providing responses. Student evaluation results also experienced an increase, namely the average score obtained in cycle I was 56.66 and in cycle II was 86.66. Based on the results of the research above, it can be concluded that the speaking ability of class X.1 students at MA Muhammadiyah Sombala Bella, Takalar Regency through the Student Facilitator and Explaining Model has increased. It is hoped that other researchers in the field of education, especially Indonesian language education, can research further on effective and efficient models for improving students' speaking skills.